Genetic variants in p53 signaling pathway genes predict chemotherapy efficacy in colorectal cancer. (15th May 2019) - Zhang, Ke; Meng, Yixuan; Cao, Xiangming; Xu, Ye; Du, Mulong; Wu, Yuan; Liu, Lingxiang
Abstract: Background: The murine double minute‐2 gene ( MDM2 ) was originally identified as predicting chemotherapy efficacy. However, little is known regarding the association between single nucleotide polymorphisms (SNPs) in the p53 signaling pathway and prognosis/chemotherapy sensitivity in colorectal cancer. Methods: We analyzed the association between 111 SNPs in 22 p53 signaling pathway genes and both progression‐free survival (PFS) and disease control rate (DCR) using Cox regression and logistics regression analysis. The false discovery rate method was used for correction of multiple testing. Secondary structure was predicted by RNAfold. Expression qualitative trait locus analysis and mRNA expression differences were assessed using the GTEx and TCGA databases. Results: We found that the rs747828 C allele of TP73 was significantly associated with reduced PFS (HR = 1.64, 95% CI = 1.27‐2.12, P = 2.00 × 10 −4 ) in the additive model. In the stratified analysis, the rs747828 C allele was significantly associated with both reduced PFS ( P = 1.40 × 10 −3 ) and DCR ( P = 1.82 × 10 −2 ) in oxaliplatin‐based chemotherapy. The secondary structure of TP73 was altered in response to different rs747828 genotypes. Although the rs747828 C allele was not associated with messenger RNA (mRNA) TP73 expression, it was significantly associated with increased mRNA TP73‐AS1 expression levels in sigmoid tissues. TP73 mRNA was significantly overexpressed in tumor tissues compared to adjacent normal tissues ( P = 2.36 × 10 −19 ). Conclusion: Our findings indicate that functional genetic variants of TP73 mediate the response to chemotherapy in colorectal cancer. Abstract : Genetic variants in TP73 mediate the response to chemotherapy in colorectal cancer. The secondary structure of TP73 was altered in different rs747828 genotypes.